Network node with wireless and wired interfaces: Nios II processor and uClinux to development of a NCAP embedded (IEEE 1451.1) with two interfaces, wireless (IEEE 1451.5) and wired (IEEE p1451.2) - Santos Filho, Tercio A. [UNESP]; Silva, Alexandre César Rodrigues da [UNESP]; Grout, Ian A.; Rossi, Silvano R. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a NCAP embedded on DE2 kit with Nios II processor and uClinux to development of a network gateway with two interfaces, wireless (ZigBee) and wired (RS232) based on IEEE 1451. Both the communications, wireless and wired, were developed to be point-to-point and working with the same protocols, based on IEEE 1451.0-2007. The tests were made using a microcomputer, which through of browser was possible access the web page stored in the DE2 kit and send commands of control and monitoring to both TIMs (WTIM and STIM). The system describes a different form of development of the NCAP node to be applied in different environments with wired or wireless in the same node. © 2011 IEEE.
Keywords: embedded system; gateway; hardware; IEEE 1451; uClinux; Control and monitoring; IEEE 1451.1; IEEE-1451; Network node; NIOS II; UClinux; Web page; Zig-Bee; Instruments; Internet protocols; Measurement theory; Standards; Telephone systems; User interfaces; Wireless sensor networks; Gateways (computer networks)